A meta-analysis of the factors affecting eWOM providing behaviour. (24th November 2020) - Ismagilova, Elvira; Rana, Nripendra P.; Slade, Emma L.; Dwivedi, Yogesh K.
Abstract : Purpose: Numerous studies have examined factors influencing electronic word of mouth (eWOM) providing behaviour. The volume of extant research and inconsistency in some of the findings makes it useful to develop an all-encompassing model synthesising results. Therefore, the purpose of this study is to synthesise findings from existing studies on eWOM by using meta-analysis, which will help to reconcile conflicting findings of factors affecting consumers' intention to engage in eWOM communications. Design/methodology/approach: The findings from 51 studies were used for meta-analysis, which was undertaken using comprehensive meta-analysis software. Findings: Factors affecting eWOM providing behaviour were divided into four groups: personal conditions, social conditions, perceptual conditions and consumption-based conditions. The results of the meta-analysis showed that out of 20 identified relationships, 16 were found to be significant (opinion seeking, information usefulness, trust in web eWOM services, economic incentive, customer satisfaction, loyalty, brand attitude, altruism, affective commitment, normative commitment, opinion leadership, self-enhancement, information influence, tie strength, homophily and community identity). Research limitations/implications: One of the limitations of this study is that the studies for this research were collected the only form from Web of Science, Scopus and Business Source such as databases, which result in a limited number of studies available for weight and meta-analysis. A wider range of databases should be used by future research. Also, this study only considered quantitative studies and excluded qualitative studies. Thus, future studies could include both types of studies in the meta-analysis. Practical implications: By focussing on the best predictors of intention to provide eWOM communications (e.g. self-enhancement and trust in web eWOM services) managers can improve reader engagement and information assimilation. Knowing motivations to engage in eWOM helps platform operators design their service in a more customer-oriented way. By better understanding motivations to engage in eWOM communications marketers and researchers can influence individuals' online information assimilation which can affect consumer purchase decisions, customer loyalty and consumer commitment to the community. Originality/value: Applying meta-analysis helped the reconciliation of conflicting findings, enabled investigation of the strengths of the relationships between motivations and eWOM providing behaviour and offered a consolidated view. The results of this study facilitate the advancement of current knowledge of information dissemination on the internet, which can influence consumer purchase intention and loyalty.